Features of the formation of a flame at a collision of two laminar gas jets - Kozlov Victor; Litvinenko Yury; Katasonov Mikhail; Shmakov Andrey (E3S Web of Conferences, 2023)
The results of studies of the interaction process of two colliding axisymmetric microjets of propane/butane mixture with and without diffusion combustion are presented. The outflow of the gas mixture was carried out through round tubes at the same velocities. During the experiment, the transverse position of the tubes was varied while maintaining the angle between them. The features of the formation of the resulting jet depending on the transverse position of the tubes are defined. When the tubes are in the same plane, the resulting jet is formed in a plane orthogonal to it. This process is observed during the interaction of burning and non-burning jets. At increasing velocity of the jets, a region of local gap of the flame front was found.